Flavonoid Compounds from the Bark of Aglaia eximia (Meliaceae) - Sianturi, Julinton; Purnamasari, Mayshah; Mayanti, Tri; Harneti, Desi; Supratman, Unang; Awang, Khalijah; Hayashi, Hideo (UI Scholars Hub, 2015)
Three flavonoid compounds, kaempferol (1), kaempferol-3-O-α-L-rhamnoside (2), and kaempferol-3-O-β-D-glucosyl-α-L-rhamnoside (3), were isolated from the bark of Aglaia eximia (Meliaceae). The chemical structures of compounds 1–3 were identified with spectroscopic data, including UV, IR, NMR (1H, 13C, DEPT 135°, HMQC, HMBC, 1H-1H-COSY NMR), and MS, as well as a compared with previously reported spectra data. All compounds were evaluated for their cytotoxic effects against P-388 murine leukemia cells. Compounds 1–3 showed cytotoxicity against P-388 murine leukemia cells with IC50 values of 1.22, 42.92, and >100 mg/mL, respectively